Avaliação da dolomita e da casca de ovo como catalisadores na oligomerização do glicerol - Barros, Fernando José Soares (2015)
Glycerol is a by-product of the biodiesel obtaining process and is highlighted due to its availability in the market and its high chemical functionality, presenting itself as a possible forerunner of a number of value-added compounds, e.g., their oligomers (di- and triglycerol). The characteristics of heterogeneous catalysts favor the transformation of glycerol valorization processes in even more sustainable routes. In this context, this paper proposes to evaluate the use of dolomite and eggshell as heterogeneous catalysts in the solventless oligomerization of glycerol. The materials were tested as catalysts in natural and calcined forms. The thermal process has modified the structure and morphology of the materials and their textural properties. Calcination was effective in increasing their catalytic activity. The calcined dolomite showed better catalytic performance, being capable of producing glycerol conversion around 97% with selectivity to diglycerol about 6,7% by reactions with a catalyst/glycerol mass ratio of 0,02; at 220 ° C, nitrogen flow and 24 hours. Using eggshells the best conditions were catalyst/glycerol mass ratio of 0,01 at 220 ° C and 24 hours, obtaining a conversion of approximately 75% and selectivity of 10,9 %. In both cases, there was formation of a high molecular weight product with non-newtonian and pseudoplastic fluid rheological behavior. Dolomite reusing tests pointed to its dissolution in the reaction product with consequent appearance of Ca and Mg in the samples, detected by ICP. There was a significant change in conversion and selectivity to diglycerol with two reuse cycles. The reaction conditions found are less severe than those reported in the literature with the use of synthetic catalysts, which added to the low cost of the material make its utilization promising in the glycerol oligomerization process